Cultural Violence against Women under Taliban Rule in Afghanistan (2021-2022) - Putri Innayah, Tazqia Kinnaree; Yulianti, Dina (Indonesia Center for Middle East Studies, 2025)
The Taliban returned to power in Afghanistan after the fall of the Islamic Republic of Afghanistan government in 2021. The Afghan government has now been transformed into the Islamic Emirate of Afghanistan (EIA). The Taliban-dominated EIA government has implemented new discriminatory and restrictive policies, particularly against women. This study employed qualitative methods, collecting data from literature reviews and interviews. Data analysis was conducted using content analysis, and validity was tested through data triangulation. The indicator of discrimination against women used in this research is SDGs No. 5 (Achieving Gender Equality and Empowering Women), in which the government should be responsible for meeting nine related targets. The conclusion of this study is that of the nine targets that should have been achieved, the Taliban have not met any of them. Using the concept of cultural violence, this condition is analyzed, and the influence of religion and ideology on the legitimacy and implementation of the Taliban's discriminatory policies against women is revealed.